Major government customers and loan contract terms - COHEN, Daniel (Institutional Knowledge at Singapore Management University, 2016)
This study examines how a firm’s business relationship with the U.S. government, in particular, sales to the government, impacts its loan contract terms and how the effect is different from that of major corporate customers. We find that firms with major government customers have a lower number of covenants and are less likely to have performance pricing provisions in their loan contracts than other firms, whereas major corporate customers do not have such impacts. We do not find evidence that major government customers affect the supplier firm’s loan spread, security, or maturity. We conjecture that lenders benefit from the strict monitoring activities of the government customer and reduce the use of covenants and performance pricing in loan contracts when the borrowing firm has a government customer.